Advanced Aluminium Products and Manufacturing Technologies Applied on Vehicles Presented at the EuroCarBody Conference. (2015) - Zhou, Jia; Wan, Xinming; Li, Yang
Abstract: The present paper deal with aluminium alloys and their manufacturing technologies (stamping, extrusion, casting, etc.) applied on vehicles on EuroCarBody from 2009 to 2013 through presentations and benchmark data. The using percentage of aluminium alloy on body in white (BIW) are summarized and analyzed. The number of vehicles using aluminium alloy are increasing from 2009 to 2013 on some kind of vehicles. More and more new technologies are adopted by using aluminium alloys to manufacture parts, With the developing of the automotive industry, more and more aluminium alloys parts will be applied on vehicles in the future. EuroCarBody is an important forum for defining and discussing the state of the art in modern series car body engineering.